Wind variability over the southeast Atlantic Ocean - Morebotsane, Kuena (Department of Oceanography, 2022)
The intraseasonal variability of low-level winds over the southeast Atlantic Ocean is investigated using high-resolution satellite derived QuikSCA T wind data spanning a 5- year period from August 1999 to July 2004. Wavelet analysis is applied to 20-70 day bandpass filtered zonal and meridional wind time series over six tropical and subtropical southeast Atlantic Ocean regions identified in previous research as being distinct. The influence of the winds over the tropical southeast Atlantic on southern African rainfall during late austral summer to early autumn (January - April) is studied. Composite analysis of QuikSCA T winds and National Center for Environmental Prediction (NCEP) re-analyses atmospheric circulation variables is performed to investigate the potential mechanisms influencing rainfall. It is found that intraseasonal wind variability over the six regions is characterised by dominant frequencies ranging between 20 and 40 days. A single spectral peak with a period that shifts from 32 days in the tropical regions (1 0-l 8.5°S) to a slightly shorter 26- 28 day period over the subtropical zones (l 9-35°S) is evident in the meridional wind spectra. The zonal wind spectra contain two main frequency peaks at 24-28 and 36-40 days. The 36-40 day frequency peak is somewhat less pronounced between 10° and 23.5°S, becoming more defined towards the south (24-35°S). The intraseasonal wind oscillations in the tropical southeast Atlantic seem to be related to convective activity over the Angola low and the West African monsoon region during late austral summer and winter, respectively. In the subtropical regions, the intraseasonal wind oscillations appear to be associated with eastward propagating midlatitude waves. Significant year-to-year variability in the intraseasonal oscillations is revealed, particularly in the timing and magnitude of dominant oscillations. Enhanced wavelet power is apparent during the 1999-2001 and 2002-2003 La Nina and El Nino events, respectively. This confirms the impact of ENSO signals over the southeast Atlantic Ocean. Westerly winds over the tropical southeast Atlantic seem to have an important influence on southern African rainfall. Generally, significantly enhanced westerly flow over thetropical southeast Atlantic coincides with increased moisture flux that feeds into the Angola low and enhanced rainfall over parts of southern Africa. The occurrence, magnitude and spatial extent of the rainfall activity seem to depend primarily on the amount of moisture inflow from the southwest Indian and tropical southeast Atlantic oceans, atmospheric circulation anomalies over southern Africa as well as the intensity of the Angola low. While the enhanced westerly winds over the tropical southeast Atlantic seem to have an influence on southern African rainfall, they do not appear by themselves to lead to above-average rainfall over the region, nor are all periods of above-average rainfall associated with enhanced westerly winds over the tropical southeast Atlantic.